2020
DOI: 10.1364/oe.385838
|View full text |Cite
|
Sign up to set email alerts
|

Alignment-free difference frequency light source tunable from 5 to 20 µm by mixing two independently tunable OPOs

Abstract: Tunable mid-infrared ultrashort lasers have become an essential tool in vibrational spectroscopy in recent years. They enabled and pushed a variety of spectroscopic applications due to their high brilliance, beam quality, low noise, and accessible wavelength range up to 20 µm. Many state-of-the-art devices apply difference frequency generation (DFG) to reach the mid-infrared spectral region. Here, birefringent phase-matching is typically employed, resulting in a significant crystal rotation during wavelength t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…They compared this method to the traditional DFG approach of mixing the signal and idler beams from a single OPA or OPO (signal-idler DFG). In this work, they demonstrated that the output power and photon efficiency of the DFG wavelength under 10 µm generated by the signal-idler DFG are higher than that of dual OPO/OPA DFG [10]. Taking the much simpler configuration of the signal-idler DFG method into consideration, Photonics 2023, 10, 505 2 of 8 this approach is a very suitable option for generating tunable 4-7 µm femtosecond lasers with tens of milliwatts average power [11].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…They compared this method to the traditional DFG approach of mixing the signal and idler beams from a single OPA or OPO (signal-idler DFG). In this work, they demonstrated that the output power and photon efficiency of the DFG wavelength under 10 µm generated by the signal-idler DFG are higher than that of dual OPO/OPA DFG [10]. Taking the much simpler configuration of the signal-idler DFG method into consideration, Photonics 2023, 10, 505 2 of 8 this approach is a very suitable option for generating tunable 4-7 µm femtosecond lasers with tens of milliwatts average power [11].…”
Section: Introductionmentioning
confidence: 90%
“…Due to the lack of mature laser gain media with emission in the mid-IR, parametric down-conversion of near-infrared (near-IR) sources through optical parametric oscillators (OPO), optical parametric amplifiers (OPA) or difference-frequency generation (DFG) remain the most efficient approaches to obtain high-power and widely tunable femtosecond mid-IR lasers [4][5][6][7]. Nowadays, there is a vast variety of research works on the generation of mid-IR lasers by parametric conversion, including intra-pulse difference frequency generation (IPDFG) [8], DFG using a dual-signal-wavelength OPO [9], and DFG between the signal and idler wavelengths of an OPA or OPO [10,11], as well as supercontinuum-seeded DFGs [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the technological infrastructure for mid‐IR spectroscopy is not as mature as its counterpart in the visible/near‐IR spectral domains, increasingly powerful yet affordable mid‐IR sources are becoming available, including QCLs, [ 185 ] optical parametric oscillators (OPOs), [ 186 ] fiber‐based supercontinuum sources, [ 187 ] and frequency combs. [ 188 ] Along with the advances in mid‐IR sources/detectors as well as the growing palette of substrate materials, researchers have also improved the performance of on‐chip mid‐IR waveguide technologies toward the vision of realizing lab‐on‐a‐chip systems.…”
Section: Advanced Integration Schemes and Functionalitiesmentioning
confidence: 99%